Adolescent information behaviour in everyday life decision making : a literature review - Kolarić, Alica (Array, 2018)
Purpose. Within the field of information science, adolescent information behaviour as a part of the general decision making process is a relatively under-examined area. The way adolescents interact with information when making decisions influences decision outcomes and consequently affects their lives. Therefore, the study of information behaviour in the decision making process is an important area for research development. The goal of this paper is to take a step to advance research in this direction by reviewing what has been learnt and offering directions for future work. Methodology. The existing publications reporting the research on adolescent information behaviour related to making everyday life decisions within the information science field were investigated using content analysis methodology. Twenty articles were selected and analysed in the following aspects: information behaviour, including information seeking, passive information acquisition and information avoidance, information sources, barriers to information seeking, information use and affective experiences. Findings. It was found that the research on the topic of decision making within the information science field is scarce. Few studies focus specifically on adolescent information behaviour for making everyday life decisions and they consider only one specific decision situation. The existing work reveals that adolescents employ a wide range of information behaviour when making decisions in everyday life, both active and passive: information seeking, passive information acquisition which encompasses passive search and passive attention, community approach, deferring information seeking and information avoidance. They use a variety of information sources, and source selection depends on internal and external factors. They face barriers which impede information seeking and use information to increase knowledge on decision situations and therefore help the decision making process.